2003
DOI: 10.1016/s0882-4010(03)00002-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in hns reduce the adherence of Shiga toxin-producing E. coli 091:H21 strain B2F1 to human colonic epithelial cells and increase the production of hemolysin

Abstract: Shiga toxin-producing Escherichia coli (STEC) 091:H21 strain B2F1, an isolate from a patient with the hemolytic uremic syndrome (HUS), produces elastase-activatable Shiga toxin (Stx) type 2d and adheres well to human colonic epithelial T84 cells. This adherence phenotype occurs even though B2F1 does not contain the locus of enterocyte effacement (LEE) that encodes the primary adhesin for E. coli O157:H7. To attempt to identify genes involved in binding of B2F1 to T84 cells a bank of mini-Tn5phoACm r transposon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Scott et al (30) performed a transposon mutagenesis in a Shiga toxin-producing E. coli (STEC) 091:H21 strain B2F1, which does not carry the LEE genes, to identify genes involved in binding to human colonic epithelial T84 cells. They found that several of the mutants displayed reduced adherence to T84 cells, and some of those mutants mapped to the hns gene.…”
Section: Discussionmentioning
confidence: 99%
“…Scott et al (30) performed a transposon mutagenesis in a Shiga toxin-producing E. coli (STEC) 091:H21 strain B2F1, which does not carry the LEE genes, to identify genes involved in binding to human colonic epithelial T84 cells. They found that several of the mutants displayed reduced adherence to T84 cells, and some of those mutants mapped to the hns gene.…”
Section: Discussionmentioning
confidence: 99%
“…The STEC strain B2F1 used in this study has two copies of stx 2d-activatable , which are referred to below as stx 2d1-activatable and stx 2d2-activatable for clarity. The plasmid-cured derivative of B2F1 no longer produces detectable hemolytic activity (40).…”
Section: Methodsmentioning
confidence: 99%
“…The global transcriptional regulator H-NS is known to bind to curved and AT-rich DNA sequences upstream of several defined UPEC virulence genes (85), including genes encoding toxins (86)(87)(88)(89) and autotransporter proteins (8,10,90). To investigate the effect of H-NS on vat transcription, the levels of Vat expression were compared by Western blot analysis of supernatant fractions prepared from WT CFT073, CFT073 vat, CFT073 vatX, CFT073 hns, and a CFT073 vatX hns double mutant (Fig.…”
Section: Transcription Of the Vat Gene Is Directly Repressed By H-nsmentioning
confidence: 99%